Intellectual Capital And Firm Value: Moderating Roles Of Tax Incentives In R&D - Wardana, Muhammad Fadhil Kusuma; Permadana, Ilham; Firmansyah, Amrie (WIM Solusi Prima, 2024)
This study investigates the effect of intellectual capital on firms’ value with tax incentives in Research and development as a moderating variable. Utilizing the moderating variable becomes the novelty of this study since research that uses the moderating variable has never been conducted. The sample used in this study is 144 firm-year companies in the manufacturing sector listed on the IDX during the 2017-2022 period. The study used panel data and multiple linear regression analysis methods with a random effect model. The result of this study indicated that intellectual capital aggregately positively affects the firms’ value. Individually, capital employed and human capital positively affect firms’ value, while structural capital does not significantly affect firms’ value. Furthermore, after the moderation, the tax incentives are proven to weaken the effect of intellectual capital aggregately and capital employed on firms’ value. Conversely, tax incentives strengthen the relationship between structural capital and firms’ value. Meanwhile, tax incentives are not moderating the relationship between human capital and firms’ value. The result of this study can be a piece of additional information for OJK to understand firms’ intrinsic value and consideration in formulating the policy about regulation and supervision.